Analisis Penyebab Ketidaksesuaian SPO Pengisian General Consent di Rumah Sakit Universitas Airlangga - Nuril Amalia; Novita Nuraini; Andri Permana Wicaksono; Rosita Prananingtias (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The incompatibility of SPO (Standart Operational Procedure) for General Consent completion was one ofmany problems that exist in the implementation of medical record activities at Airlangga UniversityHospital. SPO incompatibility in General Consent Completion could be seen from incorrect answer inGeneral Consent form for each indicator. From 21 samples of General Consent forms, there wasunsuitable answers in such as the identity of the person in charge (62%), the identity of the patient (71%),the approval for information release, privacy, personal values and patient confidence as well as thesignature and name of the witness (100%), the signature and the name of the patient person in charge(24%) and the date (43%). The purpose of this study was to analyze the cause of the SPO incompatibilityfor General Consent completion in Airlangga University Hospital. This type of research was qualitativeresearch and data collection obtained through interview. The subjects in this study were 5 registrationofficers at Airlangga University Hospital. The result of this study showed the causes of the GeneralConsent Completion SPO incompatibility were no specific training about medical records, the GeneralConsent Completion SPO did not explain the procedures to complete the form thoroughly, and there wasno socialization related to the General Consent Completion at Airlangga University Hospital. The solutionsfor this problem are, there should be an effort to improve the General Consent Completion SPO, providetraining for registration officers and conduct socialization on General Consent Completion.